Regional, demographic, and temporal trends in myeloid leukemia mortality in the United States (1999-2022): a comprehensive analysis using CDC WONDER - Lehn, Jenna; Fleming, Hannah; Billion, Taylor; Mirza, Mohsin (Frontiers in Oncology, 2025)
Myeloid Leukemias (ML) are neoplastic disorders characterized by the abnormal production of myeloid blood cells and disrupted hematopoiesis. Limited research exists on regional and demographic trends in ML mortality. This study investigates ML mortality patterns in the U.S. from 1999 to 2022, focusing on geographic and demographic disparities using age-adjusted mortality rates (AAMR) and average annual percent change (AAPC). Data were obtained from the CDC WONDER database, with AAMRs calculated per 100,000 people and stratified by region, state, urbanicity, sex, and race. AAPCs were computed using the National Cancer Institute’s (NCI) Joinpoint Regression Program (Joinpoint V 4.9.0.0, NCI). Between 1999 and 2022, there were 299,221 ML-related deaths nationwide. While most U.S. regions showed a non-significant downward trend in mortality, the Midwest demonstrated a non-significant upward trend and consistently higher AAMRs. States with the highest AAMRs included Iowa, Kansas, Minnesota, and the Dakotas—predominantly rural states. Rural areas overall had higher AAMRs than urban areas. Males and White individuals had the highest mortality across all regions, with the Midwest showing the highest AAMRs for both sexes. Although ML mortality declined significantly from 1999 to 2007, it showed a non-significant increase from 2007 to 2022, despite therapeutic advancements. Persistent disparities—particularly among rural Midwestern populations, White patients, and males—highlight the need for targeted interventions and further research to address these geographic and demographic inequities.